Conditional Duration Model and Unobserved Market Heterogeneity of Traders. An Infinite Mixture of Non–Exponentials - Gómez Déniz, Emilio; Perez-Rodriguez, Jorge (Revista Colombiana de Estadística, 2016)
This paper extends the conditional duration model proposed by De Luca and Zuccolotto (2003), proposing an infinite mixture of distributions based on non–exponentials which accounts for the unobserved market heterogeneity of traders. The model we propose takes into account the fact that reaction times follow a gamma distribution and that the intensity parameter follows the reciprocal of an inverse Gaussian distribution. This extension allows us to capture not only various density shapes of durations, but also non–monotonic shapes of hazard functions. The model also allows us to test the unobserved heterogeneity of traders. This mixture model is easy to fit and characterises the behaviour of the conditional durations reasonably well.